Dallo studio del passato allo studio di applicazioni per comunicare il passato - Sicios, Matteo (Archeomatica, 2013)
The Company "Matteo siCios – Comunicazione Dei Beni Culturali” has always dealt with Communication through the use oF technologies. in addition to the Production of videos and documentaries for Cultural heritage, to whiCh were added the techniques of video graphiss, video animation, 3D and immersive Multimedia installations for Museums and exhibitions, are developing exciting new services.one of these appli- cations are for smartophone and tablet, PerfeCt in all its parts, from design to programming, from graphic design, up to the test.